Marriage, duty and civilization: Keshab Chandra Sen and the Cuch Bihar controversy in metropolitan and colonial context. Issue 4 (1st October 2016) - Stevens, John
ABSTRACT: The marriage in 1878 of Suniti Devi, the 13-year-old daughter of the Bengali Brahmo religious and social reformer Keshab Chandra Sen, to the Maharajah of Cuch Bihar constituted one of the most controversial matrimonial events in late colonial India. The marriage controversy was significant not only in terms of its effect on religious and social reform organizations in Bengal but also in terms of the ways in which it served to challenge British attitudes towards the proper regulation of female sexuality in the empire. The British press took considerable interest in the marriage, celebrating it as an instance of the continued ability of the empire to spread civilization to India. However, this celebratory account served to occlude deeper contradictions. The contradictory character of the marriage fractured Keshab's relationship with the English Unitarians, Nonconformists and reformers who had long acted as his champions, and led to the demise of Keshabite Brahmoism as a force for national transformation in India. Through an exploration of responses to the marriage in both Bengal and Britain, this article demonstrates that varied and mutable conceptions of what constituted a male 'civilized subject' were intertwined deeply with discourses surrounding the regulation of female sexuality in both metropole and colony.